2017
DOI: 10.1007/s00520-017-4015-y
|View full text |Cite
|
Sign up to set email alerts
|

Ease of walking associates with greater free-living physical activity and reduced depressive symptomology in breast cancer survivors: pilot randomized trial

Abstract: These data support the assertion that reducing the physiological difficulty of walking may contribute to greater engagement in free-living PA, less sedentary time, and decreased psychosocial distress among BCS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 42 publications
1
6
0
Order By: Relevance
“…Multiple randomized controlled trials over the last two decades have shown structured exercise training favorably influences general health/well-being in cancer populations (Speck et al 2010). Consistent with the extensive phenotypic changes of habitual exercise, we have previously shown a modest reduction in oxygen cost of walking associated with greater free-living physical activity in BCS (Carter et al 2018). Given the known synchrony between physiological and psychological constructs, it is reasonable to suspect that improved ease of walking (i.e., ↓ difficulty) similarly contributes to greater exercise selfefficacy/confidence.…”
Section: Introductionsupporting
confidence: 78%
See 2 more Smart Citations
“…Multiple randomized controlled trials over the last two decades have shown structured exercise training favorably influences general health/well-being in cancer populations (Speck et al 2010). Consistent with the extensive phenotypic changes of habitual exercise, we have previously shown a modest reduction in oxygen cost of walking associated with greater free-living physical activity in BCS (Carter et al 2018). Given the known synchrony between physiological and psychological constructs, it is reasonable to suspect that improved ease of walking (i.e., ↓ difficulty) similarly contributes to greater exercise selfefficacy/confidence.…”
Section: Introductionsupporting
confidence: 78%
“…2005;Browning et al 2006). Since many daily tasks are performed at relatively low intensity, even modest improvements related to submaximal fitness and/or walking ease may produce meaningful benefit to independent-living (Carter et al 2018). In the present study, we reasoned that improved ease of walking would relate to increased confidence level as evidenced by favorable changes in exercise self-efficacy.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Wang et al () showed that increased CRF significantly compromised walking ability in patients with leukaemia and lymphoma. Carter, Hunter, Norian, Turan, and Rogers () revealed that improved ease of walking was associated with lower depressive symptomatology. In other words, it is assumed that the significant reduction of CRF and psychological distress in the HF group resulted in improved walking ability.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it has also been established that it is important in maintaining ease in walking in nonathletes [ 71 73 ]. This is important since ease of walking has been established as one factor that influences free living physical activity [ 64 , 66 , 74 ] and free living physical activity has profound effects on metabolic health. Muscle elasticity can also play a critical role in locomotion.…”
Section: Sarcopenia and Obesitymentioning
confidence: 99%